STRATEGIC DEVELOPMENT OF ORGANIC RICE FARM BUSINESS AT SUSUKAN DISTRICT OF SEMARANG - Tutik Dalmiyatun; Wahyu Dyah Prastiwi; Heri Setiyawan (Agricultural Socio-Economics Journal, 2018)
Go Organic program already released since 2010 by Ministry of Agriculture to increase the implementation of organic farming in Indonesia. This research was aimed to analyze the strength, weakness, opportunity and threat and also to formulate developing strategy of organic rice in Semarang Regency. Survei method with structured questionnaires were used in this research, with farmers, consumers, distributors, cooperatives’ management and government employees (Ministry of Agriculture) as the respondents. Validity and reliability test were conducted to measure the questionnaires. Data were analyzed by SWOT analysis and IE matrics. Results showed that organic rice farming in Susukan District is located on Kuadran I with coordinates (0.61; 0.95). Internal result in IE matrics is 2.69 and external one is 2.52. It means that it’s on growth stability position (concentration through horizontal integration). The developing strategy that can be implemented are as followed: increasing the production of organic farming by optimizing existing resources; maintaining the quality of organic rice products and the brand image to the communities; expanding market networks by maintaining a good relationship and cooperation; improving the distribution channels; improving marketing promotion through the media; increasing farmers’ knowledge and skills by management training and financial management; strengthening the farmers’ capital by developing the cooperative; maintaining and empowering farmers’ groups.